Studi Kasus Bimbingan dan Konseling : Penerapan Teori Pembelajaran Sosial Kognitif Albert Bandura dalam Implementasi Nilai 5S (Senyum, Salam, Sapa, Sopan, Santun) di Sekolah - Kholiza Fitri, Nur; Neviyarni S; Herman Nirwana (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Character education in elementary schools has an important role in shaping students' social behavior and life skills. One of the positive character traits of students is the 5S value (Smile, Greet, Greet, Be Polite, and Courteous). This article aims to explore the application of 5S values ​​in elementary schools using Albert Bandura's Social Cognitive Learning theory. This study uses a qualitative approach with observation and interview methods to collect data. The results of the study indicate that students can internalize the 5S values ​​through observation and modeling of behavior by teachers as well as positive reinforcement given during the learning process. The application of the 5S values ​​also shows a positive impact on the development of students' character and social relationships, where they begin to apply the attitude of smiling, greeting, greeting, being polite, and being courteous in everyday life. Overall, the application of Albert Bandura's social cognitive learning theory in this context has proven effective in improving the understanding and application of positive character values ​​in students.